Sowing date influence on the soybean tolerance to defoliation at the beginning of pod formation - Santini Leolato, Lucieli; Sangoi, Luís; Cardoso Martins Junior, Marcos; de Liz Oliveira, Vander; Durli, Murilo Miguel; Arruda de Souza, Clovis (Revista Ceres, 2023)
Late sowings anticipate flowering and decrease the soybean vegetative plasticity. These changes may limit the ability of plants to tolerate leaf area losses. The objective of this research was to evaluate the sowing date effect on soybean tolerance to defoliation at the beginning of pod formation. The experiment was set in Lages (Santa Catarina State, Brazil) during the 2016/2017 growing season. Two sowing dates were tested: November 2, 2016 (preferential) and December 15, 2016 (late). Five levels of defoliation (0%, 17%, 33%, 50% and 67%) of cultivar NA 5909 RG were imposed at the R3 growth stage. Grain yield showed a quadratic response to defoliation, ranging from 4,313 to 6,478 kg ha-1 in the preferential sowing date and from 3,374 to 4,443 kg ha-1 in the late sowing date. The plants tolerated up to 45.6% of defoliation in early sowing and 55.8% in late sowing, without yield losses, in comparison to the control. The highest level of defoliation reduced grain yield by 26.9% and 13.4% in early and late sowings, respectively, compared to the control. The delay of sowing date did not increase the sensitivity of cultivar NA 5909 RG to defoliation at the beginning of pod formation.